KLASIFIKASI SELEKSI ATRIBUT PADA SERANGAN SPAM MENGGUNAKAN METODE ALGORITMA DECISION TREE - Sudibyo, Aji; Asra, Taufik; Rifai, Bakhtiar (LPPM Universitas Nusa Mandiri, 2018)
The Internet is very okay for right now, the Internet cannot be separated from its use of email, one of the threats that occur when using email is spam, spam is a message or email is unwanted by the recipient and sent in the masses.. Research on spam attacks are derived from the dataset as much spam 4601 records comprising 1813 records are considered spam and not spam data 278 with initial attributes as much as 57 attribute with attribute class 1, wants done on using select attribute with the decision tree becomes 15 attribute with attribute class 1 conducted 3 experiments testing with percentage attribute 30%, 50% and 70% select attribute obtained the results of the select attribute features of 70% better results were obtained from 30% or 50% with accuracy values of 92,469%.